PSOE and UGT after the legislative elections of 1933 - Víctor Manuel Arbeloa (Memoria y Civilización, 2012)
After losing the elections and its parliamentary group reduced fifthy per cent, the executive committee of the Partido Socialista Obrero Español wanted to put into practice what its president, Francisco Largo Caballero, had announced and proclaimed before the election campaign, and even before leave the government of the nation, but especially during the election campaign: the social revolution, through a socialist absolute power. The first necessity of socialist executive committee was to convince the executive committee of the Unión General de Trabajadores, chaired by Julian Besteiro, tenaciously opposed till the end of January 1934, when he was defeated by the supporters of Largo Caballero. The so-called “centrists”, and especially Indalecio Prieto, actively collaborated with the majority of the party. Prieto, the best speaker and parliamentary of the party, was elected to announce the new message throughout the country in the Spanish Cortes.